2003
DOI: 10.1183/09031936.03.00031402
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of budesonide/formoterol in the management of chronic obstructive pulmonary disease

Abstract: The efficacy and safety of budesonide/formoterol in a single inhaler compared with placebo, budesonide and formoterol were evaluated in patients with moderate-to-severe chronic obstructive pulmonary disease (COPD).In a 12-month, randomised, double-blind, placebo-controlled, parallel-group study in 812 adults (mean age 64 yrs, mean forced expiratory volume in one second (FEV1) 36% predicted normal), patients received two inhalations twice daily of either budesonide/ formoterol (Symbicort1) 160/4.5 mg (delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
657
3
76

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 799 publications
(781 citation statements)
references
References 33 publications
42
657
3
76
Order By: Relevance
“…In effect, some papers have documented the advantage for COPD patients in combining long-acting anticholinergic and long-acting ß2-adrenergic agents [3][4][5][6]. Other papers [4][5][6][7][8][9][10][11][12][13][14][15] have clearly shown that both longacting ß2-agonists and inhaled corticosteroids have an important role in COPD, which increases when the two drugs are combined in the same therapeutic regimen.…”
Section: Introductionmentioning
confidence: 99%
“…In effect, some papers have documented the advantage for COPD patients in combining long-acting anticholinergic and long-acting ß2-adrenergic agents [3][4][5][6]. Other papers [4][5][6][7][8][9][10][11][12][13][14][15] have clearly shown that both longacting ß2-agonists and inhaled corticosteroids have an important role in COPD, which increases when the two drugs are combined in the same therapeutic regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed clinical benefits with ICS use in moderate to severe but not in mild COPD [33][34][35][36]. ICS use is associated with reductions in the number and severity of exacerbations experienced by patients with severe COPD [34,[36][37][38][39]. In addition, in a pooled analysis of seven randomised studies involving 5085 patients, inhaled corticosteroids reduced all-cause mortality by ∼25% relative to placebo in patients with stable COPD [40].…”
Section: Treatment Options For Copdmentioning
confidence: 99%
“…These recommendations have been based on a number of long-term (≥6 months) randomised, double-blind, placebocontrolled, parallel group trials assessing the efficacy and safety of combining a LABA with an ICS in a single inhaler [29,[37][38][39][41][42][43]. Outcome measures in these trials included lung function, symptom scores, exacerbation rates, quality of life, and safety and tolerability.…”
Section: Clinical Evidence Supporting Laba/ics Combination Therapymentioning
confidence: 99%
See 2 more Smart Citations